(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study discusses the application of the 41-time memorisation method among students at the Darussaqqof Wonomulyo Tahfidz House in Polewali Mandar Regency. The purpose of this study is to determine the application of the 41-time memorisation method in Al-Qur’an learning and to compare the fluency of memorisation between students who use this method and those who do not. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data sources include students and mentors (ustadz) at Rumah Tahfidz Darussaqqof. The results show that the 41-time repetition memorisation method is effective in improving concentration, devotion, and fluency in reading the Qur’an. Students who applied this method experienced a significant increase in memorisation strength and confidence when reading fluently and correctly. Pretest and posttest data showed an increase in reading scores after the method was applied regularly. In addition, the students’ motivation and discipline also increased, which contributed to the success of the tahfidz learning process.